Edible Medicines: An Ethnopharmacology of Food - Barbas-Rhoden, Laura (Ethnobiology Letters, 2010)
Review of Edible Medicines: An Ethnopharmacology of Food. Nina Etkin. 2006. University of Arizona Press, Tucson. Pp. 304. 24.95 (paper). ISBN 9780816527489.